Condom Tamponade in the Management of Massive Obstetric Hemorrhage: An Experience at a Teaching Hospital - Gurung, BS; Dongol, Y; Tuladhar, H (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims:This study evaluates the effectiveness of condom tamponade in the management of massive obstetric hemorrhage. Methods: This hospital based prospective descriptive study was done in the department of obstetrics and gynecology of KIST Medical College Teaching Hospital, Lalitpur, Nepal from January 2013 to December 2013. During the study period, patients with obstetric hemorrhage(>500ml blood loss) were identified and the details of the patient and their treatment were acquired. Data analysis was done by descriptive statistics using mean, median and frequency cross tabulations. The decision for condom tamponade was made when active continuous hemorrhage persisted despite of initial conservative measures. Results: Among 39 patients of obstetric hemorrhage out of 1522 deliveries, eight were managed by condom tamponade which includes 6 postpartum hemorrhage cases, 1 incomplete abortion case and 1 antepartum case managed prophylactically in anticipation of postpartum hemorrhage. Conclusions: Despite of the small study sample, the study concludes the use of condom tamponade as an effective means of controlling massive obstetrical hemorrhage due to uterine atony (both in post partum and post abortion cases). It is safe, easily available, inexpensive, minimally invasive, does not require anesthesia, easy to use and can be performed by any level of health personnel with some training. DOI: http://dx.doi.org/10.3126/njog.v9i1.11187 NJOG 2014 Jan-Jun; 2(1):41-47